Nonlinear Excitation of the Non-Wave Perturbations by the Magnetoacoustic Waves in the Non-Isentropic Plasma - Anna PERELOMOVA (Archives of Acoustics)
Nonlinear excitation of slow modes by the planar magnetosonic perturbations in a plasma is discussed. Plasma is an open system due to radiation and external heating. This may stipulate enhancement of wave perturbations and hence the acoustical activity of plasma. Plasma is assumed to be a homogeneous ideal gas with infinite electrical conductivity. The straight magnetic field is orthogonal to the velocity of fluid’s elements. Nonlinear excitation of the non-wave modes (that is, the Alfv´en and the entropy modes) by periodic and aperiodic planar magnetoacoustic perturbations, is discussed. The sawtooth wave and the small-magnitude harmonic wave are considered as examples of periodic in time perturbations. The conclusions concern acoustically active and thermally unstable flows as well.